Analisis Pengambilan Keputusan Pemberian Kredit Modal Kerja Berdasarkan Laporan Keuangan: Studi Kasus Pada PT Bank Bri (Persero) - A. Indah Anggerwati (Economics and Digital Business Review, 2024)
The Bank is one of the financial institutions that has the main function of collecting funds from the public in the form of deposits and channeling them to the community in the form of credit. This is a solution for entrepreneurs who need capital to increase their business. But the bank must be careful in channeling funds in the form of credit, so that the credit given does not become bad credit which can harm the bank. One strategy that can be done to avoid that is to analyze the financial statements of debtor to determine the financial condition of the business today and the ability of debtor to conduct their business in the future. This study aims to determine the process of analyzing the debtor's financial statements, calculating the amount of credit, and the role of financial statement analysis in supporting the effectiveness of credit at PT. Bank BRI (Persero) Tbk, Kantor Cabang Pangkep.